Surat Izin Perjalanan Dinas (SI NANAS) - Puspita, Adinda; Humaira Kudadiri , Zahra (UNIVERSITAS SERAMBI MEKKAH, 2025)
Administration of official travel records at the Faculty of Social Sciences (FIS) UIN Medan at this time. This can still be done physically and the coordinates are not yet valid, meaning that it is still set aside in several separate notes, such as making official travel orders (SPPD), fine elements of official travel costs, and compiling official travel minutes and recorded using Microsoft Office Word and Exceed Expectations applications, so changes must be made every time an official trip is made. This investigation resulted in an official travel data framework plan that can simplify the administration of official travel records so that official travel information and reports can be stored properly and accurately. With this official travel information framework, it is believed that this can minimize the shortcomings of the past framework. Management that is not yet standardized means that important information such as travel location coordinates and cost details are often ignored. This deficiency makes it difficult to track and analyze official travel data for reporting and evaluation purposes. A system that is not integrated also makes it difficult for faculties to ensure the accuracy and validity of official travel information that has been carried out. As a solution, research was conducted to design a more systematic and structured official travel data framework. This framework aims to simplify the administrative process by integrating various official travel information in one interconnected system. Information such as travel itineraries, cost details and trip results can be recorded, accessed and reported more efficiently.